PENGARUH LOCUS OF CONTROL, KOMITMEN PROFESI, BUDAYA ORGANISASI, KEPUASAN KERJA, SISTEM KOMPENSASI SERTA SIKAP INDEPENDENSI TERHADAP PERILAKU AUDITOR DALAM MENGHADAPI KONFLIK AUDIT Studi pada Auditor yang Bekerja di KAP Daerah Istimewa Yogyakarta dan Surakarta - Mei Dewi Meliana; Arif Sapta Yuniarto (Universitas Ahmad Dahlan, 2014)
This research aims to determine effect of locus of control, profession commitment, organization cultural, job satisfaction, compensation system and independence attitude for auditor behavior in face on audit conflict. The analysis based on the answer of respondents who available through of questionnaire that distribute by Yogyakarta and Surakarta Public Accountant Office. Population from the auditor research who work in the Public Accountant Office were in Yogyakarta and Surakarta. The research using the purposive sampling method. Sample taken from auditor who minimal has worked during 2 years. Cronbach Alpha used to test reliability data and testdata isused kolmogorov_Smirnovnormality. Hypothesis tested by multiple regression. Result from the research revealed that there are locus of control effect, profession commitment, organization cultural, job satisfaction, compensation system, independence attitude for auditor behavior in face on audit conflict.